Diagnosis and Management of Barosinusitis: A Systematic Review. (January 2023) - Chen, Tiffany; Pathak, Shivani; Hong, Ellen M.; Benson, Brian; Johnson, Andrew P.; Svider, Peter F.
Objective: To perform a systematic review to investigate the common presenting symptoms of barosinusitis, the incidence of those findings, the methods for diagnosis, as well as the medical and surgical treatment options. Methods: A review of PubMed/MEDLINE, EMBASE, and Cochrane Library for articles published between 1967 and 2020 was conducted with the following search term: aerosinusitis OR "sinus squeeze" OR barosinusitis OR (barotrauma AND sinusitis) OR (barotrauma AND rhinosinusitis). Twenty-seven articles encompassing 232 patients met inclusion criteria and were queried for demographics, etiology, presentation, and medical and surgical treatments. Results: Mean age of patients was 33.3 years, where 21.7% were females and 78.3% were males. Causes of barotrauma include diving (57.3%), airplane descent (26.7%), and general anesthesia (0.4%). The most common presentations were frontal pain (44.0%), epistaxis (25.4%), and maxillary pain (10.3%). Most patients received topical steroids (44.0%), oral steroids (28.4%), decongestants (20.7%), and antibiotics (15.5%). For surgical treatment, most patients received functional endoscopic sinus surgery (FESS) (49.6%). Adjunctive surgeries include middle meatal or maxillary antrostomy (20.7%), septoplasty (15.5%), and turbinate surgery (9.1%). The most efficacious medical treatments are as follows: 63.6% success rate with oral steroids (66 treated), 50.0% success rate with topical steroids (102 treated), and 50.0% success rate analgesics (10 treated). For surgical treatments received by greater than 10% of the sample, the most efficacious was FESS (91.5% success rate, 108 treated). Conclusion: Oral and topical steroids should be first line therapies. If refractory, then functional endoscopic sinus surgery is an effective treatment.